A previously undescribed jasmonate compound in flowering Arabidopsis thaliana – The identification of cis-(+)-OPDA-Ile. (February 2016) - Floková, Kristýna; Feussner, Kirstin; Herrfurth, Cornelia; Miersch, Otto; Mik, Václav; Tarkowská, Danuše; Strnad, Miroslav; Feussner, Ivo; Wasternack, Claus; Novák, Ondřej
Graphical abstract: A low-abundance isoleucine conjugate of the JA biosynthetic precursor cis -(+)-12-oxo-phytodienoic acid ( cis -(+)-OPDA-Ile) was detected in the leaves of flowering plants after local mechanical stress. Highlights: UHPLC–MS/MS analysis of jasmonates in leaf tissue of flowering Arabidopsis plants. Identification of an OPDA analog of the biologically active (+)- 7 - iso -JA-L-Ile. Cis -(+)-OPDA-Ile detection in rosette leaves of flowering Arabidopsis (Col 0, Ws). Monitoring of cis -(+)-OPDA-Ile levels in JA/JA-Ile deficient Arabidopsis mutants. Temporal dynamic endogenous cis -(+)-OPDA-Ile accumulation in wounded leaves. Abstract: Jasmonates (JAs) are plant hormones that integrate external stress stimuli with physiological responses. (+)- 7-iso -JA-L-Ile is the natural JA ligand of COI1, a component of a known JA receptor. The upstream JA biosynthetic precursor cis -(+)-12-oxo-phytodienoic acid ( cis -(+)-OPDA) has been reported to act independently of COI1 as an essential signal in several stress-induced and developmental processes. Wound-induced increases in the endogenous levels of JA/JA-Ile are accompanied by two to tenfold increases in the concentration of OPDA, but its means of perception and metabolism are unknown. To screen for putative OPDA metabolites, vegetative tissues of flowering Arabidopsis thaliana were extracted with 25% aqueous methanol (v/v), purified by single-step reversed-phase polymer-based solid-phase extraction, and analyzed by high throughput mass spectrometry. This enabled the detection and quantitation of a low abundant OPDA analog of the biologically active (+)- 7 - iso -JA-L-Ile in plant tissue samples. Levels of the newly identified compound and the related phytohormones JA, JA-Ile and cis -(+)-OPDA were monitored in wounded leaves of flowering Arabidopsis lines (Col-0 and Ws) and compared to the levels observed in Arabidopsis mutants deficient in the biosynthesis of JA ( dde2-2, opr3 ) and JA-Ile ( jar1 ). The observed cis -(+)-OPDA-Ile levels varied widely, raising questions concerning its role in Arabidopsis stress responses.